DeRisk — Accurate Prediction of ULS Wave Loads. Outlook and First Results. (September 2016) - Bredmose, H.; Dixen, M.; Ghadirian, A.; Larsen, T.J.; Schløer, S.; Andersen, S.J.; Wang, S.; Bingham, H.B.; Lindberg, O.; Christensen, E.D.; Vested, M.H.; Carstensen, S.; et al.
Abstract: Loads from extreme waves can be dimensioning for the substructures of offshore wind turbines. The DeRisk project (2015-2019) aims at an improved load evaluation procedure for extreme waves through application of advanced wave models, laboratory tests of load effects, development of hydrodynamic load models, aero-elastic response calculations and statistical analysis. This first paper from the project outlines the content and philosophy behind DeRisk. Next, the first results from laboratory tests with irregular waves are presented, including results for 2D and 3D focused wave groups. The results of focused wave group tests and a 6-hour (full scale duration) test are reproduced numerically by re-application of the wave paddle signal in a fully nonlinear potential flow wave model. A good match for the free surface elevation and associated exceedance probability curve is obtained. Finally, the utilization of DeRisk's results in practical design is discussed.